Long-Term Observation of Improvement in Liver Fibrosis Index by A Glucagon-Like Peptide-1 Receptor Agonist in A Patient with Type 2 Diabetes: A Case Report - Tokito, Akinori; Koriyama, Nobuyuki; Nishio, Yoshihiko (Archives of Clinical and Medical Case Reports, 2020)
We describe a 51-year-old man with type 2 diabetes and hepatic dysfunction with suspected nonalcoholic fatty liver disease (NAFLD)/nonalcoholic steatohepatitis (NASH). No liver biopsy was performed. His blood test showed a decrease in platelet count (PLT) of 6.3 × 104/μL. Serum levels of aspartate aminotransferase (AST) and alanine aminotransferase (ALT) were increased, and the AST/ALT ratio (AAR) exceeded 1. FIB4 index, an index of liver fibrosis, was remarkably high at 7.65. On abdominal computed tomography (CT), hepatic parenchyma was visualized as a low absorption area (CT value: 36 HU, L/S ratio <1), suggesting fat accumulation. HbA1c was 8.0%. Treatment was started with liraglutide 0.9 mg/day and changed to exenatide sustained-release formulation 2 mg/week about 1 year later. HbA1c remained around 6%. Both AST and ALT improved to the upper normal limit level, and AAR also decreased in about 2 years. Five years later, PLT increased to 13 × 104/μL and the FIB4 index decreased to 3.30. In the future, we hope that long-term and prospective studies including histological evaluation and imaging findings of NAFLD/NASH will be conducted, and that the multi-faceted, potential effects of GLP-1RA will be further clarified.